Risks of Entrepreneurship amid the COVID-19 Crisis - Tatiana N. Litvinova (Risks, 2022)
The COVID-19 crisis is unique in that it is caused by a pandemic and has created a special context for entrepreneurship in 2020. The motivation for this study is, firstly, to concretise and accurately quantify the impacts of the pandemic on entrepreneurship. Secondly, to clearly identify the specific business risks emerging or intensifying in the context of the pandemic; and thirdly, to distinguish between the impact of the economic crisis and the pandemic on entrepreneurship. This paper aims at studying the risks of entrepreneurship amid the COVID-19 pandemic and crisis. The paper’s sample consists of the top 10 countries that are leaders by the COVID-19 case rate in the world, starting 22 October 2020 up to 22 February 2022. The method of trend analysis is used to find and quantitatively measure the manifestations of the pandemic (case rate and mortality) on the entrepreneurial risks. Economic and mathematical modelling, with the help of correlation and regression analysis, showed that healthcare factors—the COVID-19 case rate and mortality—are not the key reasons for high entrepreneurial risks in 2020 and have a small influence on them. This paper’s contribution to the literature consists in specifying the cause-and-effect links between the COVID-19 pandemic and crisis and entrepreneurial risks. The theoretical significance of the results obtained consists in their proving the uniqueness of the COVID-19 crisis from the position of entrepreneurial risks. The paper’s originality consists in specifying the influence of the COVID-19 pandemic on entrepreneurial risks, explaining—thoroughly and in detail—the essence of these risks, and opening possibilities for highly-effective risk management.